1988
DOI: 10.1590/s0074-02761988000200015
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Oncophora melanocephala (Rudolphi, 1819) Baudin-Laurencin, 1971 (Nematoda, Camallanidae)

Abstract: Oncophora melanocephala, a camallanid nematode from the small intestine of Priacanthus arenatus Cuvier, 1829 is redescribed from the Coast of Rio de Janeiro State, Brazil and this occurrence represents a new host record for the species
Oncophora melanocephala, um nematóide camalanídeo de instestino delgado de Priacanthus arenatus Cuvier, 1829, é redescrito da Costa do Estado do Rio de Janeiro, Brasil, e esta ocorrência representa um novo hospedeiro para a espécie

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Brazil: Atlantic big-eye, Priacanthus arenatus Cuvier (Pinto et al 1988, Tavares et al 2001; tuna (Thunnus thynnus, T. albacares, T. atlanticus, Auxis thazard) (Moravec et al 1999); Atlantic bonito, Sarda sarda (Bloch) (Alves and Luque 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Brazil: Atlantic big-eye, Priacanthus arenatus Cuvier (Pinto et al 1988, Tavares et al 2001; tuna (Thunnus thynnus, T. albacares, T. atlanticus, Auxis thazard) (Moravec et al 1999); Atlantic bonito, Sarda sarda (Bloch) (Alves and Luque 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pinto et al (1988) reported the presence of Oncophora melanocephala Baudin-Laurencin, 1971;Fábio (2000) recorded the presence of O. melanocephala, Stephanostomum seriolae Yamaguti, 1970, Pseudopecoelus priacanthi (MacCallum, 1921, Brachyphallus parvus (Manter, 1947) and Diplectanotrema balistes Price, 1937. Tavares et al (2001 investigated the ecology of the metazoan parasite community of this fish and registered the presence of Lecithochirium sp., Opecoeloides sp., Diplectanotrema sp., Scolex pleuronectis, Polymorphus sp., O. melanocephala, Raphidascaris sp., Pseudoterranova sp.…”
Section: Introductionmentioning
confidence: 99%